2011
DOI: 10.2320/matertrans.mbw201004
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Co<SUB>2</SUB>FeAl<SUB>0.5</SUB>Si<SUB>0.5</SUB> Full-Heusler Alloy Thin Films on GaAs Substrates

Abstract: We investigated the structural and magnetic properties of Co 2 FeAl 0:5 Si 0:5 (CFAS) thin films on GaAs substrates. The CFAS thin films grew epitaxially on GaAs with CFAS (100)[100] k GaAs (100)[100] relation and formed an ordered L2 1 structure with substrate heating deposition at T SUB ¼ 300 C, 400 C and post annealed at T PA ¼ 400 C. Moreover, we confirmed the no reaction between CFAS and GaAs. The CFAS thin films on GaAs showed strong uniaxial magnetic anisotropy with an easy axis of ½110 CFAS (½110 GaAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In these measurements, a magnetic field was applied along the in-plane GaAs[110] direction, which corresponds to the magnetization easy axis of the CFAS layer. 21) It is noted that From in situ reflection high energy electron diffraction observation, it was confirmed that the CFAS layer was grown epitaxially on the n-GaAs layer with L2 1 structure. In addition, X-ray diffraction measurements and transmission electron microscopy observation revealed that there were no reactions at the CFAS/n-GaAs interface.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In these measurements, a magnetic field was applied along the in-plane GaAs[110] direction, which corresponds to the magnetization easy axis of the CFAS layer. 21) It is noted that From in situ reflection high energy electron diffraction observation, it was confirmed that the CFAS layer was grown epitaxially on the n-GaAs layer with L2 1 structure. In addition, X-ray diffraction measurements and transmission electron microscopy observation revealed that there were no reactions at the CFAS/n-GaAs interface.…”
mentioning
confidence: 83%
“…Details of the deposition conditions have already been described. 21) Note that the film in this study has low doped n-GaAs layer in order to transport polarized spins from injector to detector, in contrast, the films used for 3T-Hanle measurements in previous study has only highly doped n þ -GaAs layer. 15,16) We fabricated a 4T lateral spin transport device as shown in Fig.…”
mentioning
confidence: 95%
“…5a shows the magnetic hysteresis loops of the film after VSM heating under protective Ar gas atmosphere. The loops are obtained with the field applied along [110] and [1][2][3][4][5][6][7][8][9][10] axes in the sample Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively thick CFAS films as high spin polarized ferromagnets can enhance spin injection efficiency of the hybrid structure. CFAS films in the thickness range between 5 nm and 30 nm deposited on GaAs and Si semiconductor substrates with the insertion of MgO tunnel barrier were investigated to realize the FM/SC devices [7,8]. Recently, a large exchange bias (EB) of~240 Oe and low temperature crystallization are observed in the structure of 10 nm CFAS with antiferromagnetic IrMn 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…10,11) However, the temperature and bias voltage dependencies of spin injection signals for the CFAS/n-GaAs schottky tunnel junction have not been revealed yet.…”
Section: Introductionmentioning
confidence: 99%